Codex Alimentarius Commiáion: protecting food today and in the future - Randell, A.W.=700 1 Miyahishima, K.; Maskeliunas, J.
(Es, En, Fr.)
Ilus., 9 ref.
Keywords: CODEX ALIMENTARIUS; INOCUIDAD ALIMENTARIA; PROTECCION DE LA SALUD; ITALIA; ALIMENTACION, NUTRICION Y AGRICULTURA